Exclusive Supply Arrangement Practice Between Retailer and Supplier and its Impact to The Business Competition - Sandra Handayani Harahap (Journal of Social Research, 2025)
The exclusive arrangement on supply restriction and territorial exclusivity practices in retail business that reflected and can be found in the trading terms agreement between retailer and its supplier can be seen as a strategic behavior applied by the retailer not only with the aim to increase the profits yet also to reduce the level of competition and potentially will restraint the opportunity for such competitor to enter the relevant market and offering the same products to their customers. The consequences from such restriction should make such retailer become the exclusive seller of the products in certain territory. Although the KPPU has the authority to conduct research and investigations, the KPPU does not have the authority to conduct searches of business actors who are suspected of violating Indonesian Anti-Competition Law and in conducting research and investigations, the KPPU is often constrained by the confidentiality of the company so that the KPPU cannot obtain the necessary company data. However, it is not new phenomenon that this kind of arrangements practices can be found ongoing in the market and cannot easily be seen. Indonesian Anti-Competition Law substantially is divided into 2 (two) arrangements, namely prohibited agreements and prohibited activities, including abuse of dominant position. This research to explore the issue regarding practices of the exclusive arrangement on supply restriction and territorial exclusivity between retailer and its supplier and aims to analyzes whether this form of exclusivity agreement contrary with the Indonesian Anti-Competition Law and affecting the business competition?